Minimally Invasive Approach to the Supradiaphragmatic Inferior Vena Cava: Total Thoracoscopic Caval Isolation. Issue 2 (March 2014) - Hui, Dawn S.; Gill, Inderbir S.; Cunningham, Mark J.
Minimally invasive techniques for cardiac operations have evolved in safety and popularity. To our knowledge, a thoracoscopic technique for control of the inferior vena cava (IVC) has not been previously described. We report a case of a right renal cell cancer with tumor extension into the IVC. Total thoracoscopic isolation and occlusion of the IVC were performed. Intraoperative real-time transesophageal echocardiography confirmed complete cessation of caval flow upon cinching the Rummel tourniquet. As extensive intra-abdominal operations are more often being attempted laparoscopically or robotically, video-assisted thoracoscopic IVC occlusion for proximal control for tumors extending into the cava can be achieved to offer a minimally invasive thoracic approach.